1972
DOI: 10.1042/cs0430343
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Mechanism of the Jarisch—Herxheimer Reaction in Louse-Borne Relapsing Fever: Evidence for the Presence of Circulating Borrelia Endotoxin

Abstract: 1.Certain aspects of the Jarisch-Hemheimer reaction (JHR) after treatment of louse-borne relapsing fever have been studied in nine patients. Peripheral vasoconstriction immediately preceded the chill phase and profound vasodilation accompanied the flush phase.2. From four patients 50-150 ml of blood was taken at the onset of the chill and reinjected intravenously into the same patient the next day. One patient experienced a reaction identical with JHR 40-60 min after reinjection, suggesting that the mediator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…It is possible that some of the clinical observations and endotoxin assay data of 1 study [50] could have been confounded by concurrent (undocumented) infections which were a common problem in this particular patient group (Perine PL, personal communication, 1993).…”
Section: The Jarisch-herxheimer Reaction (Jhr)mentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that some of the clinical observations and endotoxin assay data of 1 study [50] could have been confounded by concurrent (undocumented) infections which were a common problem in this particular patient group (Perine PL, personal communication, 1993).…”
Section: The Jarisch-herxheimer Reaction (Jhr)mentioning
confidence: 96%
“…The nature of the bacterial mediator of JHR is elusive, with evidence both for [48,[50][51][52] and against [53][54][55][56] a role for endotoxin. It is possible that some of the clinical observations and endotoxin assay data of 1 study [50] could have been confounded by concurrent (undocumented) infections which were a common problem in this particular patient group (Perine PL, personal communication, 1993).…”
Section: The Jarisch-herxheimer Reaction (Jhr)mentioning
confidence: 99%
“…Blebbing of the outer membrane is said to occur A possible consequence of penicillin-induced membrane vesicle formation is the Jarisch-Herxheimer reaction, the systemic reaction that often follows treatment of relapsing fever with antibiotics (22). Some investigators have demonstrated endotoxin-like material in the sera of humans and animals with borrelial infections (6,12,31) and in the sera of humans with Jarisch-Herxheimer reaction after treatment with penicillin for secondary syphilis (13). A release of numerous blebs containing such material conceivably could precipitate the Jarisch-Herxheimer reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with current treatment guidelines [5], patients with early syphilis are recommended to receive a single dose of benzathine penicillin G; those with late latent syphilis or unknown duration are treated with 3 weekly doses of benzathine penicillin G. Following penicillin treatment of syphilis and other spirochetal diseases, a substantial proportion of patients may develop Jarisch-Herxheimer (JH) reaction, a syndrome composed of some of the following features: abrupt onset of fever, chills, myalgias, tachycardia, vasodilatation with flushing, exacerbated skin rash, or mild hypotension [6][7][8]. The reaction was described originally by Jarisch in 1895 and several years later by Herxheimer and Krause [9].…”
Section: The Incidence Of and Risk Factors For Jarisch-herxheimer (Jhmentioning
confidence: 99%